Sosialisasi Gender dalam Keluarga: Peran Orang Tua dalam Membentuk Identitas Gender Anak - Hairani Siregar; Rafli Ramadhan Ginting; Hezkia Zadina Sembiring; Putri Jeany Graciella Situmorang (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Gender socialization in the family environment plays an important role in the formation of children's gender identity from an early age. Parents as the main agents of socialization play a significant role through daily interactions, providing examples, and parenting patterns that shape children's understanding of gender roles. This study aims to determine the importance of parents' reflective awareness in supporting a more inclusive and equitable understanding of gender. This study uses a descriptive qualitative approach to examine how parents in Medan City introduce gender values ​​and norms in daily activities. The findings show that the gender socialization process is still influenced by traditional values ​​and fairly rigid gender stereotypes. The division of roles based on gender applied by parents often gives rise to the perception that gender roles are fixed and cannot be changed.